Evidence of thermophilization in Afromontane forests - Cuni-Sanchez, Aida; Martin, Emanuel H.; Uzabaho, Eustrate; Ngute, Alain S. K.; Bitariho, Robert; Kayijamahe, Charles; Marshal, Andrew R.; Mohamed, Nassoro A.; Mseja, Gideon A.; Nkwasibwe, Aventino; Rovero, Francesco; Sheil, Douglas; et al. (Nature communications, 2024)
Thermophilization is the directional change in species community composition towards greater relative abundances of species associated with warmer environments. This process is well-documented in temperate and Neotropical plant communities, but it is uncertain whether this phenomenon occurs elsewhere in the tropics. Here we extend the search for thermophilization to equatorial Africa, where lower tree diversity compared to other tropical forest regions and different biogeographic history could affect community responses to climate change. Using re-census data from 17 forest plots in three mountain regions of Africa, we find a consistent pattern of thermophilization in tree communities. Mean rates of thermophilization were +0.0086 °C·y−1 in the Kigezi Highlands (Uganda), +0.0032 °C·y−1 in the Virunga Mountains (Rwanda-Uganda-Democratic Republic of the Congo) and +0.0023 °C·y−1 in the Udzungwa Mountains (Tanzania). Distinct from other forests, both recruitment and mortality were important drivers of thermophilzation in the African plots. The forests studied currently act as a carbon sink, but the consequences of further thermophilization are unclear
Keywords: Thermophilization; Afromontane; forests